Determinan Perilaku Belanja Online di Kota Jambi - Rosmeli, Rosmeli; Ekasari, Novita; Wiralestari, Wiralestari; Saparuddin, Saparuddin; Fathiyah, Fathiyah; Alvaro, Rakan (Ekonomis: Journal of Economics and Business, 2024)
Online shopping is a trend that has spread throughout Indonesia, especially during Covid 19. This trend continues to grow today. As the capital of Jambi Province, Jambi City is an area that has the most complete internet facilities compared to other areas in Jambi Province. The availability of internet facilities and other suggestions means that online shopping in this area is quite large. This research aims to assess consumer behavior in online shopping in Jambi City; and Factors that influence online shopping in Jambi City. The analysis model used is descriptive analysis and binary logit regression model. The research results show that the average frequency of online shopping in Jambi City is 1-2 times a month. 40.2% of respondents visited 2 online sites. The e-commerce application that respondents use most for shopping is Shopee. Cheap and easy to get goods is the first reason to shop online. The more online shopping sites that are visited, the public's perception is that online shopping saves time and buying shoes/bags and accessories online are factors that have a positive and significant influence on people's online shopping in Jambi City.